KETEPATAN POLA ASUH GIZI TERHADAP KEJADIAN PENYAKIT INFEKSI PADA ANAK BATITA - Anggraini, Yeni; Cahyaningtyas, Anindhita Yudha (Bidan Prada, 2018)
The key of nutritional care patterns are giving exclusive breastfeeding and weaning food. The aim of this research is to analyze the accuracy of nutritional care patterns on incidence of infectious diseases in children under three years old in Karanganyar Regency. The type that used of this research was observational analytic. The research was conducted at Karanganyar Regency. The population were children under 3 years old. Sampling techniques that used were purposive sampling with 50 respondents. Data analysis that used was Chi Square Test. The results of this research show that the value of Chi-Square count is greater than Chi-Square table, ie 13.134> 3.84146 and p-value less than ? (0.000 <0.05), the hypothesis was accepted at the 95% confidence level and level of significance ? 0.05. The conclusion of this research is there is a significant relationship between nutritional care pattern’s accuracy to infectious diseases insidence in toddler in Karanganyar Regency. Keywords: Nutritional Care Pattern’s Accuracy, Infectious Diseases Insidence